The costs of COVID-19 and the cost-effectiveness of testing. Issue 85 (22nd February 2021) - González López-Valcárcel, Beatriz; Vallejo-Torres, Laura
Abstract : Purpose: This paper aims to provide an estimation of the costs of the coronavirus (COVID-19) pandemic with a special focus on Spain. Costs include macroeconomic costs of foregone gross domestic product (GDP) attributable to the pandemic and the direct and indirect costs of prevention, treatment and lost productivity. This study also analyzes the cost-effectiveness of the test-tracking-quarantine (TTQ) strategy in Spain. Design/methodology/approach: The macroeconomic costs of foregone GDP attributable to the pandemic are estimated for different countries and areas by comparing the present GDP forecasts for 2020 and 2021 with counterfactuals estimated before the COVID-19 crisis aftermath. The total cost of the COVID-19 for Spain in 2020 was obtained using the cost of illness approach with a bottom-up process. A cost-effectiveness analysis of the TTQ strategy in Spain is based on the estimation of the total costs of TTQ and the health gains and avoided health-care costs associated with the TTQ strategy. A sensitivity analysis explores the consequences of uncertainty in key parameters. Findings: The GDP cost of the COVID-19 is by far larger than all the other components of the cost. The global cost of the Covid-19 crisis in 2020–2021 is estimated at 14% of 2019 GDP (around 12, 206 mm$). In the specific case of Spain, it amounts to 24% of the 2019 GDP; which is 397.3 m €. Spain is and will be by far the European country most economically affected by the pandemic. In Spain 2020, the GDP cost accounts for 94.7% of the total cost of the COVID-19 and health-care direct costs are only 2.14%. TTQ is a dominant strategy in Spain. For each euro spent on it, 7 euros will be recovered only in terms of saved health-care resources. Research limitations/implications: Given the large degree of uncertainty and the fast-evolving nature of the epidemic, a number of assumptions are required to arrive at the estimates provided in this study. The results were found to be robust to the assumptions applied. Practical implications: TTQ is a key strategy for the contention of the epidemy and it is justified from the economic perspective. Originality/value: This is the first estimation of the cost of the COVID-19 and the cost-effectiveness of the TTQ strategy for Spain.